Pembuatan Kombucha dengan Variasi Nutrisi - Syafiqoh, Ainatus; Fajrin, Chamelia Muclis; Bulan, Syarifah; Isnavia, Elsa Zahrotul; Herviandari, Nanda Kirana; Kamila, Fahdhini Yusfi; Fadlia, Alfiana Dhia (STKIP HARAPAN BIMA, 2026)
This study aims to analyze the effect of nutrient variation, particularly different sugar sources, on the kombucha fermentation process. Two treatments were used: granulated sugar and palm sugar, each 50 grams in a tea solution inoculated with SCOBY and starter. Fermentation was carried out for four days at room temperature with daily visual observations and periodic pH measurements. The results showed that palm sugar caused a faster pH decrease, from 5 to 4, indicating stronger acidification activity during the early fermentation phase. In contrast, granulated sugar maintained a stable pH at 4 but successfully formed a new SCOBY layer, suggesting that sucrose more effectively supports early-stage cellulose biosynthesis. Organoleptic analysis also revealed differences in taste, aroma, and color between the two treatments. Overall, nutrient variation influenced microbial metabolic pathways, with palm sugar being more effective in promoting acid production, while granulated sugar was more optimal for cellulose formation. This study demonstrates that the choice of nutrient source plays an important role in determining the final quality of kombucha.